Pelatihan Penggunaan Aplikasi Bandicam dan Quizziz dalam Pembelajaran bagi Guru-guru SDN Menteng Atas 14 - Shobah Shofariyani Iryanti; Muhammad Arifin Rahmanto (Prodi PGSD FIP UNM, 2022)
School from home makes all learning activities carried out from home. However, the limited skills of teachers in using ICT-based learning media become an obstacle during online learning. Thus, training on the use of the Bandicam and Quizziz applications in learning for teachers of SDN Menteng Atas 14 is important to do during the Covid-19 pandemic. With this activity, it is hoped that teachers will be able to package interesting and fun learning. The method of implementing this community service activity is in the form of an online seminar. Seminar with the theme